VUS next in rare diseases? Deciphering genetic determinants of biomolecular condensation - Heredia-Torrejón, María; Montañez, Raúl; González-Menese, Antonio; Carcavilla, Atilano; Lechuga-Sancho, Alfonso María; Medina, Miguel Ángel (BioMed Central, 2024)
The diagnostic odysseys for rare disease patients are getting shorter as next-generation sequencing becomes more widespread. However, the complex genetic diversity and factors influencing expressivity continue to challenge accurate diagnosis, leaving more than 50% of genetic variants categorized as variants of uncertain significance.Genomic expression intricately hinges on localized interactions among its products. Conventional variant prioritization, biased towards known disease genes and the structure-function paradigm, overlooks the potential impact of variants shaping the composition, location, size, and properties of biomolecular condensates, genuine membraneless organelles swiftly sensing and responding to environmental changes, and modulating expressivity.To address this complexity, we propose to focus on the nexus of genetic variants within biomolecular condensates determinants. Scrutinizing variant effects in these membraneless organelles could refine prioritization, enhance diagnostics, and unveil the molecular underpinnings of rare diseases. Integrating comprehensive genome sequencing, transcriptomics, and computational models can unravel variant pathogenicity and disease mechanisms, enabling precision medicine. This paper presents the rationale driving our proposal and describes a protocol to implement this approach. By fusing state-of-the-art knowledge and methodologies into the clinical practice, we aim to redefine rare diseases diagnosis, leveraging the power of scientific advancement for more informed medical decisions.
Keywords: Enfermedades raras; Biomolecular condensation; Genetic variant prioritization; Intrinsically disordered protein regions; LLPS; Molecular diagnosis; Molecular effects of genetic variations; Rare diseases